2003
DOI: 10.1007/s00464-002-8604-5
|View full text |Cite
|
Sign up to set email alerts
|

Current status of an antireflux procedure in laparoscopic Heller myotomy

Abstract: Reflux is not necessarily eliminated with the addition of a partial fundoplication. Based on the published data, recommendations cannot be made regarding the efficacy of adding an antireflux procedure to laparoscopic Heller myotomy. Prospective randomized study is needed to clarify the role of an antireflux procedure after laparoscopic Heller myotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
5
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 34 publications
2
47
5
2
Order By: Relevance
“…In our primary analysis we assume that the LM is performed without an antireflux procedure. A literature review revealed equipoise regarding this issue [22,35,47,48] and since an antireflux procedure is not routinely added to LM at our institution, we chose not to include it in our model. We conducted a sensitivity analysis in which patients receive an antireflux procedure, which results in a lower probability of reflux.…”
Section: Decision Analytic Modelmentioning
confidence: 99%
“…In our primary analysis we assume that the LM is performed without an antireflux procedure. A literature review revealed equipoise regarding this issue [22,35,47,48] and since an antireflux procedure is not routinely added to LM at our institution, we chose not to include it in our model. We conducted a sensitivity analysis in which patients receive an antireflux procedure, which results in a lower probability of reflux.…”
Section: Decision Analytic Modelmentioning
confidence: 99%
“…70 In contrast to this, a meta-analysis was published in 2003 and included analysis of 21 studies involving 601 patients and concluded that the rates of postoperative GER were not statistically different between those with and without an antireflux procedure. 71 In fact, PPI use among those that undergo fundoplication with the Heller myotomy is 39%. 54 Further data from randomized studies indicate that there is a significant decrease in GER as measured by pH studies in those who underwent fundoplication, but there may not be a decrease in the rate of symptomatic GER.…”
Section: 68mentioning
confidence: 99%
“…Richards et al [21] in theirs randomized double-blind clinical trial comparing the outcome of myotomy plus Dor fundoplication versus myotomy alone have shown that the former operation is superior in terms of reflux control. Lyass et al [22] in their metaanalysis found that the difference in the rate of GER diagnosed in postmyotomy pH studies in wrapped and no wrapped patients was not significant (7.9 vs. 10%, respectively; p=0.75). There was also no significant difference in the incidence of postmyotomy GER symptoms in wrapped and no wrapped patients (5.9 vs. 13% respectively; p=0.12).…”
Section: Discussionmentioning
confidence: 95%